Evaluation of Hormonal Effects on Peripheral Blood Lymphocyte Apoptosis in Normal Menstruating Females (Iraqi Journal of Medical Sciences, 2016)
Background: Apoptosis is a physiological type of cell death plays an important role in the regulation and maintenance of cell populations in tissues upon physiological and some pathological conditions.Objective: To evaluate the hormonal status and peripheral blood lymphocyte apoptosis in normal menstruating female during normal menstrual cycle.Methods: 50 healthy menstruating females with regular cycles were studied. Two samples of peripheral blood were aspirated; the first during the ovulation day and the second at the first day of the menstrual cycle. Lymphocyte separation was done; by Trypan blue exclusion test, and the morphological features of lymphocyte apoptosis by the DNA binding dye (Hoechst stains). Hormonal assessments of FSH, LH, Estradiol, and progesterone were also done.Results: Lymphocyte apoptosis in the first day of cycle was (9.31%±1.7) using Trypan blue exclusion test and (9.76%±1.36) using Hoechst stain while at the day of ovulation the percentages were (2.33%±0.7) and (1.38%±0.84) respectively with P value < 0.00001. Serum level of hormones were FSH (5.76±1.77; 9.14±3.34), LH(3.65±1.4; 28.35±18.94), Estradiol (40.05±14.73; 206.38±70.3) and Progesterone (0.35±0.13; 1.41±0.98) in the first day of the menstrual cycle and during ovulation respectively which showed a highly significant difference with P value
Keywords: Lymphocyte apoptosis; FSH; LH; estrogen; progesterone; Hoechst stains